2020
DOI: 10.1109/access.2020.2988058
|View full text |Cite
|
Sign up to set email alerts
|

An Ultra-Wideband Reflective Linear-to-Circular Polarization Converter Based on Anisotropic Metasurface

Abstract: In this work, an ultra-wideband and high-efficiency reflective linear-to-circular polarization converter based on an anisotropic metasurface is proposed, which is an orthotropic structure with a pair of mutually perpendicular symmetric axes u and v along ±45 • directions with respect to the vertical y axis. The simulated and experimental results show that the polarization converter can realize ultrawideband linear-to-circular polarization conversion at both x-and y-polarized incidences, its 3dB-axialratio-band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 45 publications
0
39
0
Order By: Relevance
“…In general, the quantification of circular polarization property adopts 3-dB axial ratio (AR) relative bandwidths. 30 The value of AR can be calculated by…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, the quantification of circular polarization property adopts 3-dB axial ratio (AR) relative bandwidths. 30 The value of AR can be calculated by…”
Section: Simulation Resultsmentioning
confidence: 99%
“…It implies that the linearly polarized normal incident wave is converted into the circularly‐polarized wave and the reflected wave is a RHCP one propagating along + z direction in the operating frequency range. In general, the quantification of circular polarization property adopts 3‐dB axial ratio (AR) relative bandwidths 30 . The value of AR can be calculated by AR=Ryy2+Rxy2+aRyy2+Rxy2a1/2 wherein a = |R yy | 4 + |R xy | 4 + 2|R yy | 2 |R xy | 2 cos(2Δ φ yx ).…”
Section: Simulation and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, it has been found that metasurface can provide a convenient way to control the polarization state of EM wave. In recent years, to update the conventional design method, many different types of polarization converters have been proposed based on various anisotropic or chiral metasurfaces, which can perform different polarization conversions, such as cross polarization conversion [3][4][5][6][7][8][9][10] or linear-to-circular polarization conversion [11][12][13][14][15][16][17] . In addition, A righthanded/left-handed circularly polarized (RCP/ LCP) wave will be converted to a LCP/ RCP one after reflection on a conducting surface, however, based on a proper anisotropic or chiral metasurface, a CP-maintaining metasurface can be proposed, which can keep the handedness of the reflected wave the same as that of the CP incident one.…”
Section: Introductionmentioning
confidence: 99%
“…This requires a converter that can convert linearly polarized electromagnetic waves into circularly polarized electromagnetic waves. According to transmission type, electromagnetic wave polarization converters are divided into two types: reflective converters [1][2][3] and transmissive converters . Compared with a reflective converter, a transmissive converter can be better integrated into the system because it can be very close to the radiator device, providing a more compact system.…”
Section: Introductionmentioning
confidence: 99%